Record of zipper loach Paracanthocobitis mackenziei (Chaudhuri, 1910), an indigenous ornamental fish from West Bengal, India - Sit, Godhuli; Jana, Arun; Chanda, Angsuman; Sahu, Sanjat Kumar (Journal of Fisheries, 2023)
Paracanthocobitis mackenziei (Chaudhuri, 1910) is an ornamental fish belonging to the family Nemachilidae, mainly reported from several localities in the Ganges River basin of Uttar Pradesh and Bihar in Northern India. During a study on indigenous ornamental fish diversity in Paschim Medinipur district, P. mackenziei has been recorded for the first-time from Kangsabati River basin. The specimens have been identified based on morphometric and meristematic craracteristics. This report is the extension of the distribution of the species up to the South-Western part of West Bengal.